2016
DOI: 10.1016/j.jor.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic application of spikenard herbal rhizome decorated microstructured polymer biocomposites and their in vitro cytotoxicity

Abstract: The present study explores the synthesis of highly potential polymer biocomposite from Nardostachys jatamansi rhizome extract. The polymer biocomposites were synthesized from methyl methacrylate by free radical polymerization. ATR-IR enunciate the functional groups attributed at 956 cm(-1) (aromatic), a peak appeared at 1685 cm(-1) (-C 000000000000 000000000000 000000000000 111111111111 000000000000 111111111111 000000000000 000000000000 000000000000 O), 1186 cm(-1) (-O-CH3), 1149 cm(-1) (-C-O-C) framework and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…. Our previous report also supports this cytotoxocity study . Fluorescent images emitted green fluorescence, which indicates that the more living cells proliferation after 24 h incubation period and moreover composite did not have any adverse toxic effect leading to cell deaths .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…. Our previous report also supports this cytotoxocity study . Fluorescent images emitted green fluorescence, which indicates that the more living cells proliferation after 24 h incubation period and moreover composite did not have any adverse toxic effect leading to cell deaths .…”
Section: Resultssupporting
confidence: 86%
“…Very recently, from our group also reported that the spikenard herbal rhizome‐based polymer biocomposite could be used for orthopedic application and studied their in vitro cytocompatibility against HaCaT cell lines. More particularly, N. jatamansi decorated PMMA has been exhibit to enhance excellent cell viability in keratinocyte cell lines, also showed better activities on orthopaedic infection‐pathogens such as S. marcescens, E. coli , S. aureus, and C. trapicalis . Although, NiO is belongs to the group of transition metal oxide having good ionic conductivity and also used in several applications including batteries, electronic materials, catalyst, and electrode.…”
Section: Introductionmentioning
confidence: 99%